Dioxins and furans in breast milk: a case study of mothers from southern Rio de Janeiro, Brazil - Aldo Pacheco Ferreira; Maria de Fátima Ramos Moreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
A study of polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and polychlorinated biphenyls (dl-PCBs) was conducted in a pooled sample of breast milk from 27 primiparous mothers living in 12 locations in the meso-region industrial area of southern Rio de Janeiro, Brazil, between August 2012 and July 2013. Questionnaires with questions regarding food habits, social and economic conditions and places of dwelling were applied. Milk was collected between four and six weeks after delivery from mothers were breast-feeding only one infant. The toxic equivalency (TEQ) of PCDD/Fs, and dl-PCBs were 10.6, 4.77, 6.96 TEQ pg/g, respectively. The understanding and identification of pollution sources may be helpful for applying better counter measures against breast milk dioxin contamination. It is important for pregnant women to have a diet that is as free as possible from chemical contaminants. Further research must be undertaken in the context of epidemiological investigations to more accurately assess the effects of these compounds. The background contamination by PCDD/Fs, and dl-PCBs in mothers living at industrial area in Rio de Janeiro is lower than that generally found in industrialized countries.